Managing older patients with heart failure calls for a holistic approach. (8th April 2021) - Wiersinga, Julia H.I.; Rhodius‐Meester, Hanneke F.M.; Kleipool, Emma E.F.; Handoko, Louis; van Rossum, Albert C.; Liem, Su‐San; Trappenburg, Marijke C.; Peters, Mike J.L.; Muller, Majon
Abstract: Aims: This study aims to assess the presence of geriatric domain impairments in an older heart failure (HF) outpatient population and to relate these domain impairments with 1 year mortality risk in comparison with a geriatric outpatient population without HF. Methods and results: Data were used from two different prospective cohort studies: 241 outpatients with HF (mean age 78 ± 9 years, 48% female) and 686 geriatric outpatients (mean age 80 ± 7 years, 55% female). We similarly assessed the following geriatric domains in both cohorts: physical function, nutritional status, polypharmacy, cognitive function, and activities in daily living. Cox proportional hazards analyses were used to relate individual domains to 1 year mortality risk in both populations and to compare 1 year mortality risk between both populations. Of the patients with HF, 34% had impairments in ≥3 domains, compared with 38% in geriatric patients. One‐year mortality rates were 13% and 8%, respectively, in the HF and geriatric populations; age‐adjusted and sex‐adjusted hazard ratio (95% confidence interval) for patients with HF compared with geriatric patients was 1.7 (1.3–2.6). The individual geriatric domains were similarly associated with 1 year mortality risk in both populations. Compared with zero to two impaired domains, age‐adjusted and sex‐adjusted mortality risk (hazard ratio, 95% confidence interval) for three, four, or five impaired domains ranged from 1.6 (0.6–4.2) to 6.5 (2.1–20.1) in the HF population and from 1.4 (0.7–2.9) to 7.9 (2.9–21.3) in the geriatric population. Conclusions: In parallel with geriatric patients, patients with HF often have multiple geriatric domain impairments that adversely affect their prognosis. This similarity together with the findings that patients with HF have a higher 1 year mortality risk than a general geriatric population supports the integration of a multi‐domain geriatric assessment in outpatient HF care.